FEATURES OF CYTOKINE PROFILE DYNAMICS IN WOMEN WITH UTERINE FIBROIDS AFTER RADIOFREQUENCY ABLATION IN ORGAN-PRESERVING TREATMENT - Abdullaeva L. M.; Muminjonova I. F; Azizova Z. Sh. (Modern American Journals, 2025)
Uterine fibroids are one of the most common benign tumors in women of reproductive and perimenopausal age and are accompanied by activation of inflammatory, angiogenic, and fibrotic mechanisms. With the development of minimally invasive organ-preserving technologies, there is a growing interest in assessing the molecular effects of radiofrequency ablation (RF) on the microenvironment of the myometrial tissue.
Keywords: Uterine fibroids, radiofrequency ablation, cytokines, treatment, inflammation, angiogenesis.